Studies on the Interaction of CuI with HgClI in Solid State - Beg, Saba; Ahmad, Afaq; Varshney, Pooja (Asian Journal of Chemistry, 2016)
The reaction between CuI and HgClI in solid state has been studied by resistivity measurements, X-ray diffraction, reflectance and chemical analysis. The kinetics of the reaction has been studied by visual techniques. The reaction follows the rate law, Xn = kt, k's having the Arrhenius dependence. The reaction is diffusion controlled and is a multistep solid state ionic reaction initiated by the diffusion of HgClI molecules as such and not through counter diffusion of cations. The activation energy was found to be 56.423 ± 0.085 kJ/mol.